The Effort of the Election Supervisory Agency (Bawaslu RI) in Preventing Black Campaign on Digital Media During the 2019 Election - Anwar Ilmar; Bahirah, Hilda Indah; Rahmawati, Restu; Yuliandri, Putrawan (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
This research is motivated by the black campaign phenomenon that has occurred since the 2014 eletion and the 2017 DKI regional election, and has become increasingly widespread in the 2019 election. Bawaslu is a state institution that has the duty to monitoring the implementation of the campaign which is often filled with black campaign practices. In its implementation, Bawaslu often has difficulty to prevent the spread of black campaigns on social media. This research aims to see what makes Bawaslu unable to be optimal in preventing black campaigns on social media. This research uses a qualitative approach and the type of research used is descriptive-analytical. The concepts used are participatory supervision strategies and Michel Foucault's theory of power and knowledge. This research uses data collection techniques through interviews and literature studies in the form of books, news, and previous research journals that are relevant to this research. The results of the research show that there are determinant factors that make Bawaslu not optimal in preventing and supervising black campaigns on social media, such as the weak participatory supervision strategies made by Bawaslu. There is a power relationship that occurs between Bawaslu, social media and hoax. Because the presence and spread of hoax on social media is still stronger than the prevention efforts carried out by Bawaslu. This is because social media platforms have community standards which limit the movement and supervision of Bawaslu in dealing with hoax issues.